2013
DOI: 10.1371/journal.pone.0059620
|View full text |Cite
|
Sign up to set email alerts
|

Contradiction between Plastid Gene Transcription and Function Due to Complex Posttranscriptional Splicing: An Exemplary Study of ycf15 Function and Evolution in Angiosperms

Abstract: Plant chloroplast genes are usually co-transcribed while its posttranscriptional splicing is fairly complex and remains largely unsolved. On basis of sequencing the three complete Camellia (Theaceae) chloroplast genomes for the first time, we comprehensively analyzed the evolutionary patterns of ycf15, a plastid gene quite paradoxical in terms of its function and evolution, along the inferred angiosperm phylogeny. Although many species in separate lineages including the three species reported here contained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 55 publications
3
51
0
2
Order By: Relevance
“…We detected no structural rearrangements, IR expansions, or gene loss-and-gain events in Camellia cp genomes. And, as the previous study [93], the ycf 15 gene, employing an ATG start codon, is likely a functional gene.…”
Section: Discussionsupporting
confidence: 52%
“…We detected no structural rearrangements, IR expansions, or gene loss-and-gain events in Camellia cp genomes. And, as the previous study [93], the ycf 15 gene, employing an ATG start codon, is likely a functional gene.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, the ycf15 gene was recently presented as a new molecular marker to effectively identify Colchicum autumnale and Gloriosa superba (Nguyen et al 2015). What is more, previous studies have suggested that ycf15 is a pseudogene and not a functional gene in angiosperms (Shi et al 2013). The ycf1 reading frame is not common in plastid genes and is usually located at the boundary of the inverted repeat (IR) and the small-single copy (SSC) regions (Raubeson and Jansen 2005).…”
Section: Features Of Plastid Genomesmentioning
confidence: 99%
“…C. lineare was represented by 60 coding genes, Campynemanthe species by 5 genes, and Corsia by 5 genes in the 75-gene data matrix from the first data set. The genes infA, ycf15, and ycf68 were not included in the 75-gene data matrix because they were pseudogenes in most Liliales species examined in the present study (Shi et al 2013). The genes ycf1 and ycf2 were also excluded because high-level variations were observed in closely related taxa, which made them difficult to align.…”
Section: Phylogenetic Analysismentioning
confidence: 99%